Economia do turismo no Vale dos Vinhedos - Bento Gonçalves - RS - 1990 a 2005 - Marques, Cláudia Brazil (My University, 2014)
Tourism is known as one of the main industries in the world. It has been applied as an instrument of economic development in the Rota do Vale dos Vinhedos (Route of the Valley of Vineyards), in the municipality of Bento Gonçalves, state of Rio Grande do Sul, Brazil. In the Vale dos Vinhedos, agriculture has specialized in grapegrowing and winemaking (viticulture and viniculture). Over time, the evolution of local agriculture produced a social differentiation process. The activities currently practiced by different types of farmers and production systems in the Vale present different situations both in terms of generating economic surpluses and their distribution among the agents who participate in their appropriation, consequently causing different impacts on the dynamics of development of this theory. In methodological terms, research followed the descriptive exploratory procedure of qualitative and quantitative analysis. The central issue of the study is to look at the development of Rota do Vale dos Vinhedos during the 1990-2005 period, and to identify wine and tourism as factors that drive local economic change. It begins by discussing the evolution of each activity in the economic scene; it analyzes the indicators of participation of grape-growing and winemaking, and then establishes a counterpoint with the indicators for the tourism industry during the same period, affecting the aspect of development from the same temporal perspective. The results indicated that all the types analyzed presented positive added value margins of contribution, emphasizing the systems involving wine-making, grape growing and tourism.
O turismo tem se apresentado como uma das mais importantes indústrias mundiais. Sua aplicação como instrumento de desenvolvimento econômico da localidade da Rota do Vale dos Vinhedos, no município de Bento Gonçalves, Rio Grande do Sul, Brasil. No Vale dos Vinhedos, a agricultura especializou-se em torno da viticultura e da vinicultura. A evolução da agricultura local produziu, ao longo do tempo, um processo de diferenciação social. As atividades praticadas pelos diferentes tipos de agricultores e de sistemas de produção presentes atualmente no Vale apresentam situações distintas tanto em termos de geração de excedentes econômicos quanto de sua repartição entre os agentes que participam de sua apropriação, provocando, por conseqüência, impactos diferenciados na dinâmica de desenvolvimento desse território. Em termos metodológicos, a pesquisa seguiu o procedimento exploratório descritivo de análise quali-quantitativa. O trabalho tem como questão central estudar o desenvolvimento da Rota do Vale dos Vinhedos no período de 1990-2005 e identificar os fatores vinho e turismo como propulsores da transformação da economia local. Inicialmente discute a evolução de cada atividade no cenário da economia: analisa os indicadores de participação da vitivinicultura e a seguir faz o contraponto com os indicadores no mesmo período do setor turístico com incidência no aspecto desenvolvimento na mesma perspectiva temporal. Os resultados indicaram que todos os tipos analisados apresentam margens de contribuição de valor agregado positivas, com destaque para os sistemas que envolvem a vinificação, o cultivo de uvas viníferas e o turismo.
Keywords: Turismo; Desenvolvimento regional; Economia do turismo; Vinho e Rota Vale dos Vinhedos; Bento Gonçalves (RS); Regional development; Economy of the tourism; Wine and Vale dos Vinhedos Wine Route